The Correlation Between Urinary 8-Iso-Prostaglandin F2α and Hydrogen Peroxide Toward Renal Function in T2DM Patients Consuming Sulfonylurea and Combination of Metformin-Sulfonylurea - Sauriasari, Rani; Wulandari, Fitri; Nurifahmi, Rahmaningtyas; Sekar, Andisyah P.; Susilo, Veronika Y. (Current Diabetes Reviews, 2018)
Background: Renal dysfunction is a common complication in type 2 diabetes mellitus patients associated with oxidative damage which could be characterized by 8-iso-prostaglandin F2α and hydrogen peroxide level as oxidative stress markers. Objective: The aim of our study is to determine if there is a difference in 8-iso-prostaglandin F2α and hydrogen peroxide levels between sulfonylurea and combination of metformin-sulfonylurea in diabetic patients. We also wanted to determine if these oxidative stress markers correlate with the estimated Glomerular Filtration Rate (eGFR). Subjects and Methods: We conducted a cross-sectional study with inclusion of 55 patients with type 2 diabetes mellitus in Dr. Sitanala Tangerang Hospital, Indonesia with purposive sampling. The value of eGFR was obtained by serum creatinine levels, while the level of 8-iso-prostaglandin F2α was measured by ELISA and urinary hydrogen peroxide using FOX-1 (Ferrous Ion Oxidation Xylenol Orange 1). Results: There was no difference in 8-iso-prostaglandin F2α and hydrogen peroxide level between the two groups (p=0.088 and p=0.848). Moreover, there was no difference in eGFR values between the two groups, measured by Cockroft-Gault, MDRD, and CKD-EPI. 8-iso-prostaglandin F2α (n=55) was positively correlated with eGFR based on Cockroft-Gault (r=0.382; p=0.009), whereas urinary hydrogen peroxide (n=47) also generate significant positive correlation with eGFR based on the MDRD equation (r=0.326; p=0.021). Linear regression analysis showed that 8-iso-prostaglandin F2α is the most predictive factor and the only significant factor for eGFR in Cockroft-Gault, MDRD and also CKDEPI, even after controlled by gender, age, BMI, HbA1c, systole, and H2O2. Conclusion: The two treatments did not have any significant differences in antioxidant activity. However, an increase of urinary 8-iso-prostaglandin F2α and hydrogen peroxide which correlates with eGFR in the total sample may play a significant role in the pathophysiology of diabetic nephropathy.
Keywords: type 2 diabetes mellitus